In vivo mutagenicity evaluation of the soil fumigant 1, 3-dichloropropene. (16th July 2020) - Badding, Melissa; Gollapudi, B Bhaskar; Gehen, Sean; Yan, Zhongyu (June)
Abstract: 1, 3-Dichloropropene (1, 3-D; CAS No. 542-75-6) is a soil fumigant used for the control of nematodes in agriculture. There is an extensive database on the genotoxicity of 1, 3-D and many of the published studies are confounded by the presence of mutagenic stabilisers in the test substance. Mixed results were obtained in the in vitro assays, often due to the purity of the 1, 3-D sample tested. In order to get further clarity, the mutagenic potential of 1, 3-D was investigated in vivo in the transgenic Big Blue rodent models. Inhalation exposure of 150 ppm 1, 3-D (×2.5 tumourigenic dose) to transgenic male B6C3F1 mice did not induce lacI mutations in either the lung (tumour target tissue) or liver. Similarly, dietary administration of 1, 3-D up to 50 mg/kg/day to transgenic male Fischer 344 rats did not increase the cII mutant frequency in either the liver (tumour target) or kidney. These results, along with other available in vivo data, including the absence of DNA adducts and clastogenic/aneugenic potential, support the conclusion that 1, 3-D is efficiently detoxified in vivo and, as such, does not pose a mutagenic hazard or risk.